Phenylephrine’s (Un)certain use in Operating Theatre - Teixeira, Júlio; Órfão, Maria Rosário Matos; Marques, Anabela Azevedo (Journal of the Portuguese Society of Anesthesiology, 2019)
Intra-operative hypotension is frequent and can be an important cause of morbidity and mortality. Usually it is reversed with fluids or vasopressors. In actual practice, excessive fluid therapy is unwanted and thus pharmacological manipulation is the more reliable way. Phenylephrine, as a vasoconstrictor, is theoretically fit in hypotension cases arising from peripheral vasodilation or decreased sympathetic activity. However, reflex bradycardia and increased afterload can be harmful despite increasing blood pressure. We did a literature review on the haemodynamic effects of phenylephrine in correction of intraoperative hypotension. This narrative review was performed using the PubMed database. The following keywords were used: “phenylephrine”, “cardiac output”, “cerebral oxygenation”, “safety”, “disadvantages” and “monitorization”. The final selection was made by the authors. Phenylephrine pharmacodynamics is complex and there is evidence of opposite effects, mainly regarding cerebral oxygenation and maintenance of cardiac output. Many comparative study’s between ephedrine and phenylephrine show an advantage to the first in ptimizing both referred parameters. Such a difference fades away when the patient’s volemia is determined accordingly the Frank-Starling curve and it is on the ascending fase or plateau. When in the ascending phase, phenylephrine administration was beneficial, whereas in the plateau phase it was not. Even though there is no direct correlation reported between cerebral oxygenation and cardiac output, many authors suggest that direct dependency. Phenylephrine is effective in treating hypotension. However, the increase in blood pressure is not always asociated with the maintenance or improvement of perfusion and organic oxygenation, especially if its use is without proper monitoring. Goal-directed hemodynamic optimization will improve outcomes.